Association of a Single-Nucleotide Variant rs11100494 of the NPY5R Gene with Antipsychotic-Induced Metabolic Disorders - Vera S. Dobrodeeva; Natalia A. Shnayder; Maxim A. Novitsky; Azat R. Asadullin; Elena E. Vaiman; Marina M. Petrova; Oleg V. Limankin; Nikolay G. Neznanov; Natalia P. Garganeeva; Regina F. Nasyrova (MDPI AG, 2022)
Background: The usage of antipsychotics (APs) is the most robust and scientifically based approach in the treatment of schizophrenia spectrum disorders (SSDs). The efficiency of APs is based on a range of target receptors of the central nervous system (CNS): serotoninergic, dopaminergic, adrenergic, histaminergic and cholinergic. Metabolic disorders are the most severe adverse drug reactions (ADRs) and lead to cardiovascular diseases with a high rate of mortality in patients with SSDs. Neuropeptide Y receptor Y5 (NPY5R) is known in the chain of interaction to target receptors for APs, agouti-related peptide receptors and proopiomelanocortin receptors. We studied the association of the single-nucleotide variants (SNVs) rs11100494 and rs6837793 of the NPY5R gene, and rs16147, rs5573, rs5574 of the NPY gene, with metabolic disorders in Russian patients with SSDs. Methods: We examined 99 patients with SSDs (mean age-24.56 years old). The mean duration of APs monotherapy was 8 weeks. The biochemical blood test included levels of glucose, cholesterol, lipoproteins, alanine aminotransferase (ALT), aspartate aminotransferase (AST), total protein and albumin. Anthropometry included weight, height, waist circumference and hip circumference. We used real-time PCR to study the carriage of major and minor alleles of the SNV rs11100494 (1164C>A) of the NPY5R gene (chromosome localization-4q32.2). Group 1 comprised 25 patients with SSDs taking APs with a change in body weight of more than 6% since the start of APs therapy. Group 2 comprised 74 patients with SSDs taking APs with a change in body weight of less than 6% since the start of APs therapy. Results: We show the significance of genetic risk factors (carriage of major allele C of SNV rs11100494 of the NPY5R gene) for the development of AP-induced weight gain in Russian patients with SSDs. The allele C predisposes to AP-induced weight gain (OR = 33.48 [95% CI: 12.62; 88.82], p-value < 0.001). Additionally, the results of our study demonstrate that first-generation APs (FGAs) are more likely to cause an increase in serum transaminase levels but are less likely to increase body weight. Second-generation APs (SGAs) are more likely to cause weight gain and changes in serum glucose levels. Conclusion: Our study shows the predictive role of the allele C of SNV rs11100494 of the NPY5R gene in the development of AP-induced weight gain. However, we did not find a significant association between biochemical markers and this SNV in Russian patients with SSDs.